Dynamics of astrocytes Ca2+ signaling: a low-cost fluorescence customized system for 2D cultures - Musotto, Rosa; Wanderlingh, Ulderico; D’Ascola, Angela; Spatuzza, Michela; Catania, Maria Vincenza; De Pittà, Maurizio; Pioggia, Giovanni (Frontiers in Cell and Developmental Biology, 2024)
In an effort to help reduce the costs of fluorescence microscopy and expand the use of this valuable technique, we developed a low-cost platform capable of visualising and analysing the spatio-temporal dynamics of intracellular Ca 2+ signalling in astrocytes. The created platform, consisting of a specially adapted fluorescence microscope and a data analysis procedure performed with Imagej Fiji software and custom scripts, allowed us to detect relative changes of intracellular Ca 2+ ions in astrocytes. To demonstrate the usefulness of the workflow, we applied the methodology to several in vitro astrocyte preparations, specifically immortalised human astrocyte cells and wild-type mouse cells. To demonstrate the reliability of the procedure, analyses were conducted by stimulating astrocyte activity with the agonist dihydroxyphenylglycine (DHPG), alone or in the presence of the antagonist 2-methyl-6-phenylethyl-pyridine (MPEP).